2021
DOI: 10.15698/cst2021.01.239
|View full text |Cite
|
Sign up to set email alerts
|

Improving glucose and lipids metabolism: drug development based on bile acid related targets

Abstract: Bariatric surgery is one of the most effective treatment options for severe obesity and its comorbidities. However, it is a major surgery that poses several side effects and risks which impede its clinical use. Therefore, it is urgent to develop alternative safer pharmacological approaches to mimic bariatric surgery. Recent studies suggest that bile acids are key players in mediating the metabolic benefits of bariatric surgery. Bile acids can function as signaling molecules by targeting bile acid nuclear recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 112 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…GLP-1, mainly produced in gut endocrine cells and in the brain, is a peptide that involves in regulating gut motility, satiety, and glucose metabolism ( 25 ). GLP-1 is released after food intake and acts to amplify glucose-dependent insulin secretion, and it has been in the spotlight as a target for the treatment of obesity and diabetes as its positive effects on glucose homeostasis, appetite regulation, gastric emptying and postprandial lipid metabolism ( 26 , 27 ). In addition to TGR5, short-chain fatty acids (SCFAs), metabolites of intestinal microbiota, can promote GLP-1 secretion from L cells and improve glucose tolerance ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1, mainly produced in gut endocrine cells and in the brain, is a peptide that involves in regulating gut motility, satiety, and glucose metabolism ( 25 ). GLP-1 is released after food intake and acts to amplify glucose-dependent insulin secretion, and it has been in the spotlight as a target for the treatment of obesity and diabetes as its positive effects on glucose homeostasis, appetite regulation, gastric emptying and postprandial lipid metabolism ( 26 , 27 ). In addition to TGR5, short-chain fatty acids (SCFAs), metabolites of intestinal microbiota, can promote GLP-1 secretion from L cells and improve glucose tolerance ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…TGR5 is mainly activated by secondary bile acids, being lithocholic acid and taurolithocholic acid the most potent endogenous agonist. TGR5 activation increases energy expenditure and stimulates insulin secretion [62].…”
Section: Secondary Bile Acidsmentioning
confidence: 99%
“…As illustrated in Figure 3 , BSH primarily catalyzes the hydrolysis of endogenous steroidal natural product BAs, releasing bound BAs in the intestinal bile acid pool into free bile acids and amino acid residues ( Rimal et al., 2024 ). Numerous studies have highlighted the significance of BSH-mediated unbinding in BAs metabolism, impacting cholesterol synthesis, lipid metabolism, and glucose metabolism ( Shen et al., 2021 ; Zhu et al., 2022 ). Recent research has also revealed that BSH enzymes are involved in degrading antibiotics, in addition to their role in BAs unbinding.…”
Section: Regulation Of Natural Products By Gut Microbiome-derived Hyd...mentioning
confidence: 99%